Textural characteristics, mode of transportation and depositional environment of the Stormberg Group in the Eastern Cape, South Africa: evidence from grain size and lithofacies analyses - Chima, Priscilla; Baiyegunhi, Christopher (Sciendo and Adam Mickiewicz University, 2022)
The Stormberg Group comprises the Molteno, Elliot and Clarens formations and is one of four stratigraphical groups that make up the Karoo Supergroup in South Africa. The group is the highest unit in the Karoo Basin, representing the final phase of preserved sedimentation. The major problem with the Stromberg Group is that the mode of transport, hy- drodynamic energy conditions and depositional environment are still poorly understood. For the present paper, grain size and lithofacies studies on selected sandstones from the Molteno, Elliot and Clarens formations were performed so as to elucidate their textural characteristics, depositional processes, sedimentation mechanisms and hydrodynamic energy conditions and to discriminate different depositional environments. The statistical parameters of grain size distribution (mean grain size, standard deviation, skewness and kurtosis) show that the sandstones are predominantly unimodal, fine grained, moderately well sorted, mesokurtic and near symmetrical. The bivariate diagrams of the afore- mentioned statistical parameters demonstrate that river and aeolian dune had the greatest impact on the depositional environments. Likewise, the C-M pattern (Passega diagram) shows that the sandstones were mostly deposited through tractive current process. Furthermore, the C-M diagram reveals the prevalence of rolling, suspension and graded sus- pension modes of sediment transportation. Seventeen sedimentary lithofacies were identified and grouped into seven lithofacies associations. These lithofacies associations indicate braided channel, overbank and swamp deposits for the Molteno Formation, alluvial fan/floodplain and playa deposits for the Elliot Formation and aeolian deposits for the Clarens Formation.